2017
DOI: 10.1016/j.molcel.2017.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Regulates Protein Methylation during Stress Responses in Plants

Abstract: Methylation and nitric oxide (NO)-based S-nitrosylation are highly conserved protein posttranslational modifications that regulate diverse biological processes. In higher eukaryotes, PRMT5 catalyzes Arg symmetric dimethylation, including key components of the spliceosome. The Arabidopsis prmt5 mutant shows severe developmental defects and impaired stress responses. However, little is known about the mechanisms regulating the PRMT5 activity. Here, we report that NO positively regulates the PRMT5 activity throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 43 publications
3
85
0
Order By: Relevance
“…S-nitrosylation mediated by NO represents a key process in plant growth and development, as well as responses to environmental changes (Hess et al, 2005;Kovacs & Lindermayr, 2013;Hu et al, 2017;Zhan et al, 2018)…”
Section: Messenger Molecules Involved In Cold Signal Transductionmentioning
confidence: 99%
“…S-nitrosylation mediated by NO represents a key process in plant growth and development, as well as responses to environmental changes (Hess et al, 2005;Kovacs & Lindermayr, 2013;Hu et al, 2017;Zhan et al, 2018)…”
Section: Messenger Molecules Involved In Cold Signal Transductionmentioning
confidence: 99%
“…However, the PRMT5 C125S transgenic plants are hypersensitive to NaCl and ABA, but insensitive to NO that enhances resistance to stress, indicating that S ‐nitrosylation at Cys‐125 is essential for the PRMT5‐regulated stress responses. Moreover, salt stress‐induced arginine symmetric demethylation is also abolished in PRMT5 C125S transgenic plants, correlated to aberrant pre‐mRNA splicing of stress‐related genes (Hu et al ). This study illustrates the importance of the crosstalk between S ‐nitrosylation and arginine methylation in modulating stress responses.…”
Section: Abiotic Stress Responsesmentioning
confidence: 99%
“…It has been reported that plants transduce NO signal through S‐nitrosylation of protein arginine methyl transferase 5 involved in protein methylation machinery and the subsequent epigenetic regulation of pre‐mRNA splicing, DNA damage repair, and mRNA translation (Blanc & Richard, ) in response to environmental alterations (Hu et al, ). It is worth mentioning that the polycomb repressive complex 2 subunit VERNALIZATION 2 is regulated, like ERFVIIs, in an O 2 ‐ and NO‐dependent manner involving the Cys–Arg branch of the N‐end rule proteolytic pathway (Gibbs et al, ), thus representing an additional support for a functional link between NO signaling and epigenetic regulation.…”
Section: No Sensing and Phytohormone Signalingmentioning
confidence: 99%